2022
DOI: 10.3390/ijerph191912275
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Long-Term Care Insurance on Medical Utilization and Expenditures: Evidence from Jingmen, China

Abstract: The purpose of this study was to evaluate the impact of long-term care insurance (LTCI) on medical utilization and expenditures in Jingmen, a pilot city of China. The propensity score matching-difference in difference (PSM-DID) approach was employed to examine the expenses and frequency of inpatient and outpatient services before and after the implementation of the LTCI based on the 2015–2018 panel data from the China Health and Retirement Longitudinal Study (CHARLS). The results showed that the annual expendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…However, the combination of rapid socioeconomic change, an ageing population, the one-child policy and other demographic shifts, is eroding the ability and capacity of the family-based system to care for the older population in China [ 4 ]. Moreover, long-term care costs for older people are not currently covered by national healthcare insurance schemes [ 5 ] and only older people without children are eligible for places in government-funded public care homes [ 6 ]. Although some aged care insurance pilot programmes have been implemented in several cities from 2016, studies have since found that such programmes are often fragmented in their coverage, eligibility, funding and reimbursement [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the combination of rapid socioeconomic change, an ageing population, the one-child policy and other demographic shifts, is eroding the ability and capacity of the family-based system to care for the older population in China [ 4 ]. Moreover, long-term care costs for older people are not currently covered by national healthcare insurance schemes [ 5 ] and only older people without children are eligible for places in government-funded public care homes [ 6 ]. Although some aged care insurance pilot programmes have been implemented in several cities from 2016, studies have since found that such programmes are often fragmented in their coverage, eligibility, funding and reimbursement [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, long-term care costs for older people are not currently covered by national healthcare insurance schemes [ 5 ] and only older people without children are eligible for places in government-funded public care homes [ 6 ]. Although some aged care insurance pilot programmes have been implemented in several cities from 2016, studies have since found that such programmes are often fragmented in their coverage, eligibility, funding and reimbursement [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the reduction in financial burdens, Lei et al (18) further found that LTCI improves older people's selfreported health and reduces their mortality risks. However, these studies mainly focus on only one pilot city (13,32). The study on China's LTCI is still not enough, especially the limitation on older adults' mental health and spillover effects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Testing for a potential placebo effect was necessary to rule out the effects of other exogenous events (such as healthcare reform measures like the critical illness insurance program) and confirm that the findings were the result of LTCI. Drawing on the work of relevant scholars [71,72], we took 1000 random samples to represent the two study groups, and the specific kernel density distribution results are shown in Figure 5. Most of the absolute values of the estimated coefficients of sampling "t-values" were within the value of 2, and the "p-values" were above 0.1.…”
Section: Placebo Effectmentioning
confidence: 99%